Polysaccharide Hydrogels with Waste Wool Fibre as Matrix for Potential Use as CRF Fertiliser - Ewa Szczepanik; Edyta Molik; Kinga Pielichowska (Molecules, 2025)
At a time of climate change, farmers face difficulties in providing food for a growing population. This results in the overuse of water and fertilisers. The aim of the research was to test the possibility of introducing waste sheep wool fibres into a hydrogel to obtain a stable material that could improve water retention and could serve as a fertiliser material matrix. Wool fibres and hydrogel were chosen because of their ability to store water and their degradability. An evaluation of the swelling degree of different alginate-based hydrogel matrices was performed to select the matrix. The stability and water bonding of hydrogels with different wool fibre content were analysed and evaluated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The microstructure and the effect of fibres on the uniformity of the hydrogel were assessed using SEM and optical microscopy. The degree of water retention in the soil was also evaluated. The results showed that it is possible to incorporate wool fibres into the hydrogel matrix and the wool fibres make the composite porous, which allows water penetration into the material much more easily. This research has shown the possibility of using waste wool fibres as an active ingredient in sustainable fertiliser materials.